IDECOL: Efficacy of an intervention with children at risk of dyslexia in a professional setting using a single-case experimental design - Palazón López, Julián; Avilés Martínez, Pablo; Cortés Sandoval, Amanda Fabiola (Revista de Investigación en Logopedia, 2024)
Although research has shown that it is possible to improve the decoding of children with dyslexia, few studies have reported this in real-world settings where resources are limited. In this study, through the development of a single case experimental design with multiple baselines, the application of the IDECOL program was evaluated in three children at risk of dyslexia who showed severe decoding difficulties. The intervention addressed the following key aspects for improved decoding: a) direct instruction of the alphabetic principle, b) decoding, c) phonemic awareness, d) frequent spelling recognition, and e) repeated readings. The children received one 55-minute session per week for 12 weeks. After designing a baseline in which the intervention was not applied, the children's improvement in reading was repeatedly monitored. The improvement in the decoding of the three children was immediate after the application of the first session and the effect found was extensive after the twelve sessions. After the intervention was withdrawn, two of the three children suffered a regression or stagnated in the improvement of their decoding skills, which supports that the effects found were due to the application of the program. The results support that an individualized and broadly specialized intervention applied in real contexts can be effective with relatively low exposure in young children who show significant decoding difficulties.
Keywords: dyslexia; dyslexia treatment; reading difficulties